Managerial delegation in a dynamic renewable resource oligopoly - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2015)
I propose a differential oligopoly game of resource extraction under (quasi-static) open-loop and nonlinear feedback strategies, where firms are managerial and two alternative types of delegation contract are considered. Under open-loop information, delegation expands the residual steady state resource stock. Conversely, under nonlinear feedback information the outcome depends on the structure of managerial incentives. If sales are used, once again delegation favours resource preservation. On the contrary, if market shares are included in the delegation contract, this combines with an underlying voracity effect in shrinking the steady state volume of the resource.
Keywords: C73; L13; Q2; 330